Peran Asean Ministrial Meeting On Transnational Crime Dalam Penanggulangan Perdagangan Manusia di Indonesia - Muhammad Asy Ari Badar; Agussalim Burhanuddin (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
. This research investigates the involvement of the ASEAN Ministerial Meeting on Transnational Crime (AMMTC) in efforts to tackle human trafficking in the ASEAN region, with a focus on the role and concrete steps that have been taken in supporting the fight against human trafficking in Indonesia. Using a qualitative approach with literature study methods, data was collected from various literature sources including official ASEAN documents, research reports and academic articles. The research results show that human trafficking is one of the most serious transnational crime issues in the ASEAN region, with the main victims including vulnerable women and children. AMMTC plays a role in developing policies and legal frameworks to address human trafficking, as well as facilitating operational cooperation between law enforcement agencies of ASEAN member countries. Concrete steps taken by AMMTC include issuing the ASEAN Action Plan to Combat Transnational Crime, adopting implementation guidelines, and formulating ACTIP (ASEAN Convention Against Human Trafficking in Persons). Through these steps, ASEAN is demonstrating a strong commitment to confronting the issue of human trafficking and working with member countries to address the threat. This research contributes to a deeper understanding of the role of AMMTC in combating human trafficking in the ASEAN region and its relevance to efforts to combat human trafficking in Indonesia.